Musical Elegy, the history of its origin. (Eurasian Journal of Learning and Academic Teaching, 2023)
Life is not only along, but also a difficult path, which requires considerable effort to overcome. It consists of trial and error, as well as happy and sad events, to which a person responds extremely emotionally. In this regard, people of art were very lucky: writers, artists and composers. They can turn any experienced feeling into an object of universal admiration. So, for example, a poet, in order to express his mental suffering, composes a touching lyric poem and calls it "Elegy". However, the musical work has the same name, in which the composer subtly displays the entire gamut of human experiences not with verses, but with sounds.